Repetitive transcranial magnetic stimulation in combination with neuromuscular electrical stimulation for treatment of post-stroke dysphagia - Zhang, Chengliang; Zheng, Xiuqin; Lu, Rulan; Yun, Wenwei; Yun, Huifang; Zhou, Xianju (Journal of international medical research, 2019)
Objective This study was performed to determine whether repetitive transcranial magnetic stimulation (rTMS) combined with neuromuscular electrical stimulation (NMES) effectively ameliorates dysphagia and how rTMS protocols (bilateral vs. unilateral) combined with NMES can be optimized. Methods Sixty-four patients were randomly divided into four groups using a random distribution table: the sham rTMS plus NMES (Sham-rTMS/NMES), ipsilesional 10-Hz rTMS plus NMES (Ipsi-rTMS/NMES), contralesional 1-Hz rTMS plus NMES (Contra-rTMS/NMES), and bilateral rTMS plus NMES (Bi-rTMS/NMES) groups. Cortical excitability as measured by the amplitude of the motor evoked potential at the mylohyoid muscle cortical representative area, swallowing function as measured by the Standardized Swallowing Assessment, and the degree of dysphagia were evaluated at baseline, after the stimulation course, and at the 1-month follow-up. Results Bi-rTMS/NMES produced higher cortical excitability and better swallowing function recovery. Compared with NMES alone, unilateral rTMS plus NMES had additional effects on cortical excitability and rehabilitation of dysphagia, but there were no differences between the Contra-rTMS/NMES and Ipsi-rTMS/NMES groups. No adverse events occurred. Conclusion The combination of rTMS with NMES was superior to NMES alone in improving the recovery of post-stroke dysphagia, and the combination of bilateral rTMS with NMES was more effective than unilateral rTMS combined with NMES.